A formação continuada do diretor de escolas de educação infantil de 0 a 3 anos - Sousa, Juliana Aparecida Purificação de (Universidade Federal de São Carlos, 2022)
The objective of this research was to analyze the Continuing Education of the Director in schools from 0 to 3 years old, for the process of strengthening the professionalization of teaching in Early Childhood Education, having as research field the Municipality of Cabreúva/SP. The interest in the subject arose from the observation that the School Director of this segment often requests support and specific investment for their training in the area of activity, taking into account the particularities existing in their work context. This research uses a qualitative, descriptive and interpretive approach. For the construction of data, a questionnaire (Google Form) was used with directors or deputy directors of this segment. To compose the deepening of the research data, semi-structured interviews were carried out with two directors of Early Childhood Education from 0 to 3 years old in Cabreúva: the first, Effective Director of the network with the longest career in the School Directorate and the second Substitute Deputy Director in the career start. The analysis is based on studies on continuing education and career (NÓVOA, 2017), school management (LÜCK, 2000) and Early Childhood Education Maria Malta Campos. For data analysis, analytical categories were constructed referring to the Principals of Early Childhood Education, namely: training profile; Professional Experience and Professionalization and Continuing Training in Service. The main results indicate that it is necessary to expand the discussions regarding training needs, taking into account the specificities of the context of managers from 0 to 3 years old and Public Policies for Specialized Training to consolidate the professionalization process. The data also indicate the need to offer a follow-up program for the Novice Director, taking into account the specificities faced for work at the beginning of the career.
The continuing education of the director of early childhood education schools from 0 to 3 years old
Keywords: Diretor escolar; Formação continuada; Educação infantil de 0 a 3 anos; Profissionalização; School director; Continuing educacion; Early childhood education from 0 to 3 years old; Professionalization; CIENCIAS HUMANAS::EDUCACAO